The Ceylon economy : from the great depression to the great boom - Indraratna, A. D. V. de S. (Colombo : M. D. Gunasena, 1966)
It analyses how cyclical fluctuations in economic activity originating in Ceylon's' markets abroad have affected her domestic economy through foreign trade; second to show the extent to which it has been possible to insulate the domestic economy from their impact, given her existing fiscal structure.
Includes bibliographical references.
kjo 17/01/2019
Loans
Keywords: Fiscal policy; Business cycles; Sri Lanka